DISTRIBUIÇÃO ESPAÇO-TEMPORAL DE FLEBOTOMÍNEOS E DA LEISHMANIOSE VISCERAL EM ÁREA DE TRANSMISSÃO INTENSA, CAMPO GRANDE, MS, BRASIL - Wagner de Souza Fernandes (2021)
The disturbances in the environment caused by the disorderly opening of new areas to meet the growing demand of the population, including those with low socioeconomic conditions and living in precarious sanitary conditions, favor the emergence or re-emergence of several vectorborne diseases, such as the leishmaniases. The city of Campo Grande, located in the Midwestern Brazil, is classified as an intense transmission area for visceral leishmaniasis (VL), with the first notifications in 2001, followed by strong expansion in the area in the following years. The present study aimed to identify the spatio-temporal distribution of sandflies and VL in the city of Campo Grande, Mato Grosso do Sul, and to understand how urbanization has altered the local fauna of these Diptera. We used primary fauna data obtained through systematic collections performed with the help of automatic light traps installed every fifteen days in sixteen neighborhoods, from July 2017 to June 2019. Secondary data from works carried out in the urban area between the years 1999 and 2000 and 2003 to 2005 were also used. The Normalized Difference Vegetation Index (NDVI) was used to calculate the percentage of urbanized area between 1999 and 2017 and climate variable data to assess the influence of abiotic factors on the abundance and distribution of these insects. To evaluate the distribution of VL, the incidence and description of the demographic characteristics of the population were calculated. Reported cases were geocoded and grouped by neighborhood to estimate smoothed relative risks and evaluated according to area data analysis using Generalized Additive Model. Between 2017 and 2019, 1572 sandflies belonging to four species were captured: Bichromomyia flaviscutellata, Evandromyia lenti, Lutzomyia longipalpis and Nyssomyia whitmani. A reduction in about 85% of the species previously found in the city was observed. Lutzomyia longipalpis, with 99.4%, was the most frequent and dominant species. The species frequency correlated with mean temperature, humidity and wind speed, and the seasonality observed showed that the risk of infection by Leishmania (Leishmania) infantum in the area occurs throughout the year. The sampled environments showed an increase in urbanized areas in the last 20 years. In line with the other results, we evidenced the rapid transition from epidemic to endemic areas and the centrifugal dispersion pattern of VL in Campo Grande, and that the urban quality of life index, calculated based on data of income, education, housing conditions and environmental sanitation are determinants in the occurrence of the disease. We emphasize that understanding the relationship of sandflies with environmental changes and socioeconomic conditions of a population is essential to understand the dynamics of leishmaniases, seeking to provide subsidies to propose and implement measures to prevent and control the disease.